Evaluation of Tahfizhul Qur'an Learning in Madrasah Ibtidaiyah’s as a Premier Program - Fatoni, Mahfud Heru; Subando, Joko (Journal of Elementary Educational Research, 2024)
This study aims to analyze the implementation of the Al-Qur'an memorization learning program at MITQ Al Manar Klaten. The research method used is qualitative with an evaluation approach. The evaluation model applied is the CIPP model. The results of this study are that the implementation of the Al-Qur'an memorization learning program at MITQ Al Manar has not been fully in accordance with the initial plan. The memorization target set was not achieved, on average students were only able to memorize 1-2 Juz from the target of 3 Juz. Supporting factors for the implementation of the program include the enthusiasm of teachers in improving the skills of tahsin and tahfizh Al-Qur'an, parental support, integration of the tahfizh program into the school's vision and mission, teacher commitment to improving the ability to read and memorize the Al-Qur'an, and good communication between teachers and parents. Inhibiting factors include budget constraints, teacher quality, new students, teacher absenteeism, teacher teaching skills, parents' ability to read the Al-Qur'an, limited school facilities, many students whose parents work, and lack of student awareness to carry out muraja'ah independently. The Qur'an memorization program at MITQ Al Manar has not achieved the set memorization target, although supported by teachers, parents, and the school's vision, but is constrained by budget factors, teaching quality, limited facilities, and low student awareness to muraja'ah independently. The findings of this study can be used as a reference and pilot model in developing the Qur'an memorization program at other institutions, by prioritizing the quality and success of students in memorizing the Qur'an.